EVALUATION OF EXTRACTS OF QUALEA PARAENSIS DUCKE FOR THEIR ANTIMICROBIAL, TOXIC AND ANTICHOLINESTERASE ACTIVITIES (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Popularly known as red mandioqueira, ‘mandioqueira vermelha’, Qualea paraensis Ducke is a plant species belonging to the family Vochysiaceae, with a natural distribution in the Amazon region. It is used in traditional medicine, by native communities of the Amazon and Bolivia, for the treatment of skin lesions caused by microorganisms. Previous studies of the species have found antimalarial activity in vivo assays. However, studies involving the investigation of numerous biological activities of Q. paraensis are incipient. Biological assays already performed with plants of other species of the genus Qualea have shown promising biological activities. Therefore, this study describes the evaluation of the biological activities (bactericide, fungicide, toxicity, and anticholinesterase) of an ethanolic extract of the bark of Q. paraensis from the state of Roraima, Brazil. For the evaluation of the toxicity of the extract, a system with microcrustacean Artemia salina was used. Antimicrobial activity was tested for the pathogenic groups of fungi (Aspergillus flavus and Fusarium proliferatum), Gram-negative bacteria (Escherichia coli and Salmonella tiphymurium), and Gram-positive bacteria (Staphylococcus aureus and Streptococcus sanguinis). The potential of the extract for the inhibition of the enzyme acetylcholinesterase (AChE) was also evaluated. The assays for determining the antimicrobial activity for Gram-positive bacteria revealed satisfactory IC50 (29.98μg/mL) inhibition values for S. sanguinis strains, showing inhibition of 64.6% of their growth. The assay for S. aureus, however, presented low inhibition. For Gram-negative bacteria, there was moderate inhibition of E. coli strains. The extract showed low toxicity to A. salina and inhibition of 23.66% of the AChE enzyme.